2019
DOI: 10.1002/jcsm.12431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative body compositions on survival following resection of biliary tract cancer

Abstract: Background Although surgical resection is the only potentially curative treatment for biliary tract cancer, the prognosis remains poor after a major operation such as pancreatoduodenectomy or hepatectomy. We aimed to investigate the impact of preoperative body compositions on long‐term survival of patients undergoing resection of biliary tract cancer. Methods We analysed data of patients diagnosed with biliary tract cancer who underwent surgery from 2009 to 2015. Skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…However, sarcopenia was significantly associated with poor prognosis in the univariate analysis. Concordant with our data, Yoon et al, who analyzed the significance of sarcopenia on BTC, showed that a low skeletal muscle index was not associated with improved survival in a multivariate analysis ( 30 ). It is possible that BTC is more affected by tumor specific factors rather than patient related factors such as sarcopenia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, sarcopenia was significantly associated with poor prognosis in the univariate analysis. Concordant with our data, Yoon et al, who analyzed the significance of sarcopenia on BTC, showed that a low skeletal muscle index was not associated with improved survival in a multivariate analysis ( 30 ). It is possible that BTC is more affected by tumor specific factors rather than patient related factors such as sarcopenia.…”
Section: Discussionsupporting
confidence: 92%
“…Yoon et al used two ways to evaluate the sarcopenia status of BTC patients; skeletal muscle attenuation; and index. They also suggested that those with low skeletal muscle attenuation had negative influence on survival when compared to those that underwent resection for BTC ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Along with these analyses suggesting a use of L3SMI, L3PMI, and MMA as stand-alone markers for estimating patients’ overall survival, we further tested different combinations of L3SMI/MMA as prognostic markers, revealing that patients with low muscle mass and low muscle quality had the worst prognosis of all patients ( Figure 6 ). Interestingly, these data are in line with a recent analysis by Yoon et al, demonstrating that both reduced muscle mass and muscle quality are indicative for an impaired prognosis of patients following the resection of biliary tract cancer [ 23 ]. In the past, reduced muscle mass, e.g., indicated by a reduced L3SMI or L3PMI, was used to assess the presence of sarcopenia.…”
Section: Discussionsupporting
confidence: 89%
“…Sarcopenia is associated with multiple medical issues such as disability, prolonged hospitalization, increased inflammatory marker levels, postoperative complications, falls, and poor quality of life [8][9][10][11]. In addition, using computed tomography (CT)-based analysis, which is one of the most commonly used methods for evaluating muscle mass, recent studies reported that sarcopenia is a risk factor associated with poor survival of patients with various types of tumors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%